Research on spatiotemporal changes and driving factors of ecosystem service value in Ningxia Hui Autonomous Region - Chao, Mengjun (Transactions on Environment, Energy and Earth Sciences, 2024)
With the continuous development of society, people gradually shift from focusing on "food and clothing" to focusing on "environmental protection." This study studies the spatiotemporal changes in land use, ecosystem service value (ESV) and the change-driving mechanisms, with the purpose of caring for the sustainable development of Ningxia. Provide reasonable suggestions to policymakers to ensure the rational and scientific development of the Ningxia Hui Autonomous Region. This article adopts long-term dynamic analysis of the Ningxia region. In order to ensure that the sample data analysis results are closer to reality, the sensitivity index (CS) is introduced to reasonably evaluate the ESV equivalent coefficient table, and the principal component analysis method (PCA) is used to determine the relationship with ESV changes. The most relevant drivers. The results show: (1) Between 1985 and 2000, a large amount of Barren, grassland and cultivated land flowed to Impervious, and the ESV decreased by 103 million yuan. After 2000, the area of forest continued to increase, and the changes in the area of cultivated land and grassland tended to be stable. In Ningxia, local The total amount of ESV shows a rising trend, and ESV increased by 3.1807 billion yuan (2) from 1985 to 2020, mainly due to the increase in the total population and the increase in per capita GDP, which led to a weakening of the ESV increase trend, and even a reverse growth trend. Between 2000 and 2020 Due to the increasing emphasis on the ecological environment, the total amount of ESV continues to grow, but the growth rate continues to slow down.